International Continence Society Good Urodynamic Practices and Terms 2016: Urodynamics, uroflowmetry, cystometry, and pressure‐flow study. Issue 5 (5th December 2016) - Rosier, Peter F.W.M; Schaefer, Werner; Lose, Gunnar; Goldman, Howard B.; Guralnick, Michael; Eustice, Sharon; Dickinson, Tamara; Hashim, Hashim
Abstract : Aims: The working group initiated by the ICS Standardisation Steering Committee has updated the International Continence Society Standard "Good Urodynamic Practice" published in 2002. Methods: On the basis of the manuscript: "ICS standard to develop evidence‐based standards, " a new ICS Standard was developed in the period from December 2013 to December 2015. In July, a draft was posted on the ICS website for membership comments and discussed at the ICS 2015 annual meeting. The input of ICS membership was included in the final draft before ICS approval and subsequent peer review (for this journal). Results: This evidence‐based ICS‐GUP2016 has newly or more precisely defined more than 30 terms and provides standards for the practice, quality control, interpretation, and reporting of urodynamics; cystometry and pressure‐flow analysis. Furthermore, the working group has included recommendations for pre‐testing information and for patient information and preparation. On the basis of earlier ICS standardisations and updating according to available evidence, the practice of uroflowmetry, cystometry, and pressure‐flow studies are further detailed. Conclusion: ICS‐GUP2016 updates and adds on to ICS‐GUP2002 to improve urodynamic testing and reporting both for individual care and scientific purposes.